Manuel Josef Ramos, quinterón y escribano real de las Indias. Anatomía de un proceso de movilidad social en el Panamá colonial tardío - Mamadou Makaya Diaw (Nuevo mundo - Mundos Nuevos, 2018)
This article aims to analyze the different steps of a social mobility process carried out by a quinteron named Manuel Josef Ramos, highlighting the strategies used by him to overcome the legal and social obstacles encountered along the way. It also endeavors to demonstrate that the quality of quinteron or Brown did not constitute an impediment to the performance of public positions, in this case the pen trades.